Servant leadership, trust and implications for the "Base-of-the-Pyramid" segment in South Africa - A. Chatbury; D. Beaty; H. S. Kriek (South African Journal of Business Management, 2011)
This paper examines the relationship between servant leadership and interpersonal trust in South Africa. The results of this empirical investigation, conducted among low level employees and their managers, revealed a statistically significant relationship between servant leadership and interpersonal trust using Spearman's r-value of 0.664 (p 0.05). These findings will be discussed in terms of their implications for establishing what kind of leadership model might work at the Base of the Pyramid (BOP) and how this approach might build trust among stakeholders in the informal economy in South Africa.
Keywords: 650